EVALUATION OF THE EU-FUNDED PROJECT ON THE EMPOWERMENT OF WOMEN FROM AFGHANISTAN - Altenova, Madina; Goncsarenko, Karina; Hussain, Safdar (Nazarbayev University Graduate School of Public Policy, 2025)
The purpose of this study is to examine the 2019 EU-funded project on the empowerment of Afghan women via training and education. In this research, we analyze the project's development, implementation, stakeholder issues and challenges, as well as broader implications for gender equality in post-conflict areas, such as that of Afghanistan. A qualitative methodology is used to analyze documents, as well as conduct in-depth interviews with key stakeholders, including EU representatives, UNDP officials, partner university administrators, who are all part of the initiative. The two-phased project was aimed at providing Afghan females with higher education opportunities and future career prospects. Findings show that the implementation of the project was rather smooth and the participants who participated were successful in their studies. However, following the Taliban’s return to power in Afghanistan in 2021, the project changed immensely and the reintegration of females into Afghan society and job market became close to impossible; thus, most females seek to build a new life and use their skills abroad. Findings highlight the need for enhanced post-graduation support for participants, as well as more flexible and adaptable implementation strategy to accommodate shifting political landscapes. This study serves as a project evaluation paper, with a target demographic of scholars and policymakers actively involved in international development and gender studies. This research also enhances the discussion on women's empowerment and provides valuable insights into the intricacies of implementing extensive programs in developing nations.
Keywords: Type of access: Open access; Women empowerment; EU-funded project; Project evaluation; Afghanistan; Women empowerment in Afghanistan; Higher education; Central Asia; Post-conflict development; Gender equality; Afghan women; Kazakhstan